2017
DOI: 10.1007/s40261-017-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Expression of O6-Methylguanine-DNA Methyltransferase (MGMT) and p53, and the Clinical Response in Metastatic Pancreatic Adenocarcinoma Treated with FOLFIRINOX

Abstract: These preliminary findings suggest that for patients treated with FOLFIRINOX as a first-line treatment for metastatic pancreatic adenocarcinoma, the immunohistochemical evaluation of MGMT could not predict the clinical outcome; however, the survival was not significant probably because of the under-powered study (due to small sample size). A strong tumor expression of p53 is associated with a poor prognosis of OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In a study conducted in 2017, the findings of the study performed for the relation between P53 and MGMT genes on patients with metastatic pancreatic adenocarcinoma showed that MGMT expression was significantly lower in cell lines where P53 gene was mutated. It is observed that when P53 gene is positive, MGMT expression occurs at a lower level than P53 expression level, and when P53 gene is negative, MGMT gene expression was significantly lower [23].…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted in 2017, the findings of the study performed for the relation between P53 and MGMT genes on patients with metastatic pancreatic adenocarcinoma showed that MGMT expression was significantly lower in cell lines where P53 gene was mutated. It is observed that when P53 gene is positive, MGMT expression occurs at a lower level than P53 expression level, and when P53 gene is negative, MGMT gene expression was significantly lower [23].…”
Section: Discussionmentioning
confidence: 98%
“…Because of the semiquantitative characteristics of IHC and the discordance of scoring standards, 16,22,23 we referred to previous studies on ovarian carcinoma 24 and compared p53 staining to next-generation sequencing of tumor tissue as the criterion standard reference. We found that 3-tier p53 expression had a moderate correlation with 3 genotypes of TP53, as the previous report 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in TP53 increase the stability and accumulation of the p53 protein, immunohistochemical staining for p53 is not related to the overall survival of patients with PDAC who undergo complete pancreatic resection [59,60,97]. However, in patients with metastatic pancreatic cancer treated with FOLFIRINOX, high levels of p53 expression in the tumor are significantly correlated with a poor overall survival rate but not a poor PFS or response rate [98].…”
Section: Tp53 Mutations In Pancreatic Cancermentioning
confidence: 98%